Właściwy Tor . biuletyn informacyjny NSZZ "Solidarność" Kolejarzy Pomorskiego OKP, no. 6, 1981 - "Solidarność", [ed. Henryk Jarząbek, Jan Tarnowski, Ewaryst Waligórski] (NSZZ "Solidarność" Kolejarzy Pomorskiego OKP, 1981)
Creation and circulation: For organizational use; After introduction of the Martial Law publication suspended. Republished in 1989